THE CONTRIBUTION OF THE PHYSICAL CHEMISTRY DEPARTMENT TO RESEARCH OF METALLICAL MELTS: UDC 532.74:539.26. (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2007)
The condition of structural researches a metallic melts i in the world, in Ukraine and in the physical-chemistry faculty is reviewed.
Keywords: -